Life cycle and morphological descriptions of Helopeltis theivora Waterhouse (Hemiptera: Miridae) - Shovon Kumar Paul,; Nur Azura Adam,; Syari Jamian,; Anis Syahirah Mokhtar, (Penerbit Universiti Kebangsaan Malaysia, 2025)
The tea mosquito bug, Helopeltis theivora Waterhouse, is a serious pest of tea that damages buds, young shoots, and tender leaves mainly in Asian countries, including Malaysia. It is essential to understand the life cycle of this insect pest in order to apply the most effective management techniques. Therefore, the study aimed to gain a better understanding of the life cycle of H. theivora. The life cycle study of H. theivora showed that the incubation period was 8.40±0.15 days and the nymphal duration was 15.20±0.96 days, underwent five nymphal instars characterized by the length of the antenna. The mean longevity of adult females was 37.23±1.65 days, whereas for adult males was 29.11±0.92 days. The total life cycle of the females and males lasted 60.83±3.45 days and 52.71±4.33 days, respectively. On average, each female produced 156.47±16.33 eggs, with the sex ratio male to female was 1:1.09. The length and width of eggs were 1.134±0.02 mm and 0.283±0.01 mm, respectively, with two unequal respiratory horns at the tip. The first and second instar nymphs were light orange, and later instars were greenish to green. The full-grown fifth nymphal instar measured at 4.65±0.03 mm body length and 7.20±0.02 mm antennal length. Males and females of H. theivora were differentiated by the size of the body. The pronotal collar was bicoloured in both sexes. The findings of this study could be useful to formulate an effective management program against this pest.